Abordagem do professor de inglês sobre identidade docente: uma análise em diários dialogados - Silva, Francisco Everlândio de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
The teaching-learning of English language, the teaching identity of the English teacher and the construction of this identity are crucial subjects, nowadays discussed by diverse areas of studies. Considering the complex teaching-learning system, we must take into account, especially when dealing with foreign language teaching, the importance of studying teaching approaches as these increasingly seek to provide a better result in this system. In order to better focus and conceptualize teaching approaches, we support the studies of Richards and Rodgers (1999), Almeida-Filho (1993), Oliveira (2014), Silveira (1999), Vilaça (2008) and Sousa e Soares; on the basis of which we shaped our idea of approach and brought its historical importance to language teaching. Also, the teaching approaches and the construction of their identity (GATTI, 1996; GUIMARÃES, 2004; NÓVOA, 1992), since the perception of oneself in pedagogical practice has implications in the teaching-learning process of the English language. Because of this, it was necessary to ask: What is the English teacher's approach to his teaching identity, recorded in dialogues diaries? We used the dialogue diaries (ZABALZA, 2004; HAMMOUTI, 2002; DIAS, 2011; MACHADO, LOUSADA and ABREU-TARDELLI, 2007) to analyze the teaching approach and its influence on teacher identity construction. After analyzing the excerpts taken from the dialogue diaries, we noticed that there is a predominance of the traditional/grammatical approach to teaching, but we also perceive the presence of the communicative approach, once the first one is already well established as part of an identity already formed up the production of the diaries, the second is the most important in the (re)construction of a new act, an identity that is in the process of being built. In this way, we perceive the diaries as a potential instrument for the perception of the teaching activity, as well as an unparalleled source for identification and presentation of the main teaching approaches that are presented as essential pillars in the construction of the teaching identity.
Keywords: Abordagem; Identidade; Diários; Docência; Língua Inglesa; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS INGLESA